2017
DOI: 10.1097/md.0000000000006536
|View full text |Cite
|
Sign up to set email alerts
|

A new method for estimating the prevalence of clonorchiasis in Korea

Abstract: South Korea presently uses an arbitrary sampling method to monitor the prevalence of Clonorchis sinensis infection in the endemic areas of the country. However, the present method is not standardized and focuses primarily on individuals who reside nearest to the mainstream river. We propose a new sampling method that combines cluster sampling with proportionate quota sampling to ensure that the entire endemic area is accurately represented. We tested the new method in Okcheon-gun, South Korea, and determined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…This suggested that the prevention C. sinensis infection in rural areas should not be neglected. We found that distance to the nearest water bodies had a negative effect with C. sinensis infection, consistent with knowledge that inhabitants living closer to waterbodies had more chance of freshwater fish consumption ( Jeong et al, 2017; Lai et al, 2017 ). The above finding suggested the rural elderly population in the river basins should be prioritized for effective control and prevention of C. sinensis infection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This suggested that the prevention C. sinensis infection in rural areas should not be neglected. We found that distance to the nearest water bodies had a negative effect with C. sinensis infection, consistent with knowledge that inhabitants living closer to waterbodies had more chance of freshwater fish consumption ( Jeong et al, 2017; Lai et al, 2017 ). The above finding suggested the rural elderly population in the river basins should be prioritized for effective control and prevention of C. sinensis infection.…”
Section: Discussionsupporting
confidence: 90%
“…Of note, CEP seemed effective in certain sense, at least the overall infection risk did not increase but remain stable since 2005. In practice, the CEP started in different times across different areas with different intensity of implementation, which may lead to different local trends of infection risk ( Jeong et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that surveys using FE or combined the two diagnostic methods (i.e., FE and Kato-Katz) tended to report higher prevalence than that using Kato-Katz method, in line with the previous studies. 30 Distance to the nearest water bodies was found negative associated with infection risk, consistent with knowledge that inhabitants living closer to waterbodies had more chance of freshwater fish consumption, 18 , 21 suggesting that residents living in the river basins should be prioritized for effective control and prevention of the disease. Our results showed that the infection risk was negatively associated with HII, indicating the disease was more common in areas with low levels of human activities, which tended to be remote, poorly educated, and economically underdeveloped.…”
Section: Discussionsupporting
confidence: 55%
“…In practice, the two national programs started in different times in different areas with different intensity of implementation, which may lead to different local trends of infection risk. 15 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation